Delayed diagnosed Gradenigo's syndrome associated with acute otitis media - (:unkn) unknown (SAGE PUBLICATIONS INC, 2020)
Gradenigo's syndrome presents as a triad of retroorbital pain, ipsilateral abducens palsy, and purulent otorrhea. If the otologic pathologies in Gradenigo's syndrome go unnoticed, the condition could be misdiagnosed with neurological diseases because of retroorbital pain and abducens palsy. Treatment of Gradenigo's syndrome remains controversial. Although some reports state that long-term antibiotic treatment is sufficient, we recommended that management ought to be guided on a case-by-case basis depending on patient and disease factors. Herein, we report a delayed diagnosed pediatric case of Gradenigo's syndrome associated with acute otitis media that was treated with ventilation tube insertion.
Keywords: Gradenigo's syndrome; petrous apicitis; abducens palsy; acute otitis media; PETROUS APICITIS